Cadastro ambiental rural como instrumento da administração pública para a proteção do meio ambiente sob a perspectiva da democracia deliberativa de Habermas - Oliboni, Luiza Maria (My University, 2018)
This work seeks to check, through the analysis of the process of creation and implementation of the Rural Environmental Registry from Habermas deliberative democracy perspective, the possibility of this tool to become an object of public policy, providing an effective environmental protection. It also aims to investigate the goals of the Rural Environmental Registry as a tool of Public Administration in its reactive and proactive functions, using as approach its context, including issues about the Forest Code of 2012, law in which the Rural Environmental Registry is envisaged, to later describe its main aspects. These include the Rural Environmental Registry as embodiment of the right to environmental information, its function in the fight against deforestation and as requisite for joining the Program for Environmental Regularization, besides its roll in the environmental zoning. It is also done an analysis of the process of implementation of the Rural Environmental Registry in Caxias do Sul under the perspective of Habermas theory. In this context, the work explains elements about the procedure, principles and forms of execution of this theory. It is adopted the hypothectical-deductive methodology, using bibliographic and documentary techniques. As results of this research, it is possible to highlight the conclusion about the multiplicity of potentialities of the Rural Environmental Registry that may become a basis for several actions and environmental protection policies, such as the real possibility and urgent necessity of expanding, improving and consolidating deliberative mechanisms in the taking of public decisions, as well as in the implementation of environmetal public policy in Brazil.
Este trabalho busca verificar, por meio da análise do processo de criação e implementação do Cadastro Ambiental Rural a partir da perspectiva da democracia deliberativa de Habermas, a possibilidade de tal instrumento se transformar em objeto de políticas públicas que proporcionem uma proteção ambiental efetiva. Tenciona também investigar as finalidades do CAR enquanto instrumento da Administração Pública em suas funções reativa e proativa, utilizando como abordagem a contextualização do referido instrumento, incluindo questões relativas ao Código Florestal de 2012, lei na qual está inserido, para posteriormente descrever seus diferentes aspectos. Estes compreendem o CAR como materialização do direito à informação ambiental, sua função de combate ao desmatamento e pressuposto do Programa de Regularização Ambiental, além de seu papel no zoneamento ambiental. Também é feita uma análise do processo de implementação do Cadastro Ambiental Rural em Caxias do Sul à luz da teoria de Habermas, da qual são explicitados elementos referentes ao procedimento, princípios e formas de aplicação. A metodologia adotada é a hipotético-dedutiva, utilizando as técnicas de pesquisa bibliográfica e documental. Como resultados da pesquisa, destacam-se a constatação acerca da multiplicidade de potencialidades do CAR, que pode servir de base para diferentes ações e políticas de proteção ambiental, assim como a real possibilidade e urgente necessidade de ampliar, aprimorar e consolidar mecanismos deliberativos na tomada de decisões públicas, bem como na implementação de políticas públicas de cunho ambiental no Brasil.
Keywords: Habermas, Jürgen, - 1929-; Registro de imóveis - Brasil; Propriedade rural; Democracia deliberativa; Política pública; Meio ambiente; Direito ambiental; Lan titles - Registration and transfer - Brazil; Farm ownerships; Deliberative democracy; Public policy; Environment; Environmental law